Passive mixing on microfluidic devices via dielectric elastomer actuation - McDaniel, Kevin Jerome (Kansas State University, 2008)
Mixing is an essential process to many areas of science for example it is important in studying chemical reaction kinetics, chemical synthesis, DNA hybridization and PCR amplification. Mixing on the macroscale level is readily achieved through convection. Rapid mixing on microchips however, is problematic as the low Reynolds numbers and high Peclet numbers indicate that fluid flow is in the laminar regime and limits mixing on microchips to diffusion. Because of these limitations mixing on microchips is often relegated to diffusional mixing which requires long channels and long time periods. Several methods have been developed to increase the speed and efficiency of mixing on microfluidic devices. A variety of techniques have been employed to overcome these obstacles including for example 1) 3 dimensional channel designs to split up and recombine flows 2) employing sophisticated lithographic techniques to make grooves within a channel to generate transverse flows and 3) using lateral flow created by using spiral channels. Other groups have used outside energy sources to achieve mixing by changing of the zeta potential within the channel, using induced charge electroosmosis, and also by modifying the electrokinetic flow. We propose using dielectric elastomers (DEs) to modulate flow as a means to achieve rapid and active mixing on the microchip format. Electroactive polymers such as poly(dimethylsiloxane) function as DEs and are capable of converting electrical energy into mechanical energy. The application of an electrical potential across the PDMS results in a change in the dimensions of the PDMS dielectric layer between the two actuating electrodes creating an actuator. When employed in microfluidic devices this actuator can be used to change the volumes of the microfluidic channels on the PDMS. If the actuators are placed near a T-intersection where two components are entering the intersection the actuators can serve to improve mixing on microfluidic devices. Studies were conducted on how on the magnitude of the actuation, the frequency of actuation, the field strength, the electrode design and position relative to the T intersection, the channel dimensions and the overall channel design impacted mixing efficiency. Mixing results showed promise but further development of technology is necessary to achieve adequate mixing in microfluidic channels using DEs.
Keywords: Microfluidics; Mixing; Chemistry, Analytical (0486)